Sustainable Microfinance and Global Performance Proposal for a Decision-Making Support Tool - Hamdani, Siham; Ibenrissoul, Abdelmajid (European Journal of Sustainable Development, 2017)
Outreach and financial sustainability are “the two basic drivers” of the microfinance industry. These two missions seem contradictory and their complementarity is the main challenge of microfinance institutions (MFIs) around the world. A challenge that is still current and in the center of debates between two opposing theoretical visions; the social welfare approach and the institutionalist approach, which Morduch refers to as the “schism of microfinance”. In other words, MFIs are exposed to tradeoffs between their two objectives, with the risk of prioritizing sustainability, which may be at the cost of outreach; their reason for being. Whence, the central question of this research: Is a balance between outreach and sustainability possible? The objective of this paper is to study, both theoretically and empirically, MFIs’ performances in terms of outreach and sustainability, as well as the trade-offs that may exist between them, with the aim of finding answers to this issue of balance between social and commercial missions, still unresolved. Thus, the ultimate contribution of this research is the “Global Performance Indicator”; a decision-making support tool that measures MFIs’ performances with regard to outreach and sustainability, as well as the interaction of these two variables, and consequently orients the decision-makers towards the actions to be taken in order to balance social and commercial objectives. To answer the research problem, we studied the case of two large nationwide microcredit associations in Morocco (AMCs) serving those excluded from the traditional banking system, and two small AMCs targeting mainly very low-income populations. This study supports the hypothesis concerning the positive links and complementarity between outreach and sustainability, while relying on governance as a strategic and decisive stake in the effectiveness of an institution. Keywords: microfinance, sustainability, outreach, global performance